2018
DOI: 10.1016/j.chemosphere.2018.04.128
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of perfluoroalkyl acids by heat-activated persulfate under conditions representative of in situ chemical oxidation

Abstract: Perfluoroalkyl acids (PFAAs) are a class of organic contaminants notable for their extreme persistence. The unique chemical properties of these compounds make them difficult to remove from water using most standard water treatment techniques. To gain insight into the possibility of remediating contaminated groundwater by in situ chemical oxidation with heat-activated persulfate, PFAA removal and the generation of transformation products were evaluated under laboratory conditions. Solution pH had a strong influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 48 publications
6
78
2
Order By: Relevance
“…In a first report, Briton et al conducted batch experiments on groundwater and aquifer sediments spiked with two different AFFs formulations to assess the removal efficacy of heat activated persulfate. Here, heat-activated persulfate under acidic conditions led to the conversion of fluorotelomer-based and sulfonamide-based PFAA precursors into PFCAs, which were eventually mineralized, with a marked effect on 6:2 FtTAoS, consistently with other findings from the same authors [292]. By contrast, the treatment was poorly effective against other PFSAs (i.e., PFOS and PFHxS) revealing also the impossibility of mass balance determination of fluorine content.…”
Section: Remediation Technologies For Treatment Of Pfas-contaminated ...supporting
confidence: 83%
See 1 more Smart Citation
“…In a first report, Briton et al conducted batch experiments on groundwater and aquifer sediments spiked with two different AFFs formulations to assess the removal efficacy of heat activated persulfate. Here, heat-activated persulfate under acidic conditions led to the conversion of fluorotelomer-based and sulfonamide-based PFAA precursors into PFCAs, which were eventually mineralized, with a marked effect on 6:2 FtTAoS, consistently with other findings from the same authors [292]. By contrast, the treatment was poorly effective against other PFSAs (i.e., PFOS and PFHxS) revealing also the impossibility of mass balance determination of fluorine content.…”
Section: Remediation Technologies For Treatment Of Pfas-contaminated ...supporting
confidence: 83%
“…The authors concluded that heat-activated persulfate might be useful to remediate soil contaminated by AFFFs containing PFCAs or fluorotelomer-based PFAS but not other types [293]. The remediation with heat activated persulfate appears to be much more problematic in case of PFOS since poor [294] or no defluorination has been observed even under acidic conditions and high persulfate doses [274,292]. In general, the use of heat activated persulfate has some important drawbacks including the generation of undesired byproducts, including short chain PFCAs and the mobilization of heavy metals into the aquifer due to its acidification.…”
Section: Remediation Technologies For Treatment Of Pfas-contaminated ...mentioning
confidence: 99%
“…; Rodriguez‐Freire et al ; Wood et al ). Advanced oxidizing processes (AOPs) are discussed as some literature describes the sequential defluorination of long‐chain PFCAs (specifically PFOA), but AOPs are largely inefficient for mineralization of PFAS (Bruton and Sedlak ) and have not been successfully demonstrated to attack or mineralize the perfluoroalkyl sulfonates (PFSAs).…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%
“…According to the research results, the authors of [15] found that the introduction of the third component in the composition of the powder mixture will allow the formation of layers with the necessary properties on the surface of the products. The most promising is the process of complex saturation with boron, chromium and aluminum, when it is possible to minimize the energy costs of the process and get the maximum effect from improving product quality.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%